2005
DOI: 10.1108/02632770510602388
|View full text |Cite
|
Sign up to set email alerts
|

Modelling water closet demand in shopping centres

Abstract: PurposeTo quantify water closet (WC) provisions in shopping malls in order to help building professionals to determine effective sanitary designs at certain service standards in terms of the user's probable waiting time.Design/methodology/approachThe proposed WC provision takes account of the probable waiting time corresponding to certain demand patterns of shopping malls. The probable waiting time for a WC and the failure rate of the closet in providing immediate service to the users at various WC provision l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…The existing methodology does not refer to the arrival patterns from the design occupant load patterns in shopping centres. 13,14 In respect to the statutory requirements stating that an appliance is designated to serve a number of occupants, installations of WC appear to be satisfactory with the selection of the maximum allowable failure rate. However, due to this inadequacy of sanitary facilities, it has been reported that in some shopping centres there is a longer waiting time to obtain sanitary services.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The existing methodology does not refer to the arrival patterns from the design occupant load patterns in shopping centres. 13,14 In respect to the statutory requirements stating that an appliance is designated to serve a number of occupants, installations of WC appear to be satisfactory with the selection of the maximum allowable failure rate. However, due to this inadequacy of sanitary facilities, it has been reported that in some shopping centres there is a longer waiting time to obtain sanitary services.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to this inadequacy of sanitary facilities, it has been reported that in some shopping centres there is a longer waiting time to obtain sanitary services. 14 Additional WCs have actually been installed in some shopping centres to reduce the probable amount of time for waiting at peak demands, thus enhancing the overall service of those centres. Additional provisions were determined by professional designers but without further feedback from users, the performance of each provision was still indefinable.…”
Section: Introductionmentioning
confidence: 99%